Characteristics of tertiary lymphoid structures in prostate cancer and the impact of neoadjuvant therapy on their formation and maturation - Liu, Shengzhuo; Yu, Yunfei; Zhou, Jing; Yang, Lucheng; Yan, Xin; Liu, Xiaoyang; Ma, Kai; Liu, Liangren; Wang, Xianding; Zhao, Chengjian; Dong, Qiang (Frontiers in Immunology, 2025)
SynopsisTertiary lymphoid structures (TLSs) are linked to better outcomes in prostate cancer. Neoadjuvant hormone therapy enhances TLS formation, immune cell infiltration, and tumor response—supporting the potential of combining hormone and immunotherapy for improved treatment.PurposeThis study investigates the characteristics and prognostic significance of tertiary lymphoid structures (TLS) in prostate cancer (PCa), and explores the impact of neoadjuvant hormone therapy (NHT) on TLS formation and maturation.Materials and methodsTLS features and immune infiltration were assessed in PCa cohorts using H&E and multiplex immunohistochemistry (mIHC) for Ki67, panCK, CD21, CD4, CD8, and CD20. Public datasets compared TLS signatures between NHT-treated and NHT-naïve patients, and between paired pre-/post-NHT samples. An orthotopic immunocompetent PCa mouse model was generated using organoids and CRISPR-Cas9. Flow cytometry evaluated immune infiltration in bicalutamide-treated mice, and anti-PD1 was combined with degarelix/bicalutamide in preclinical mouse model.ResultsTLS were detected in 93% of NHT-naïve PCa tissues, predominantly within tumors. Mature TLS, secondary follicle-like TLS (SFL-TLS), and higher intra-tumoral TLS density correlated with prolonged progression-free survival (PFS). NHT-treated patients exhibited elevated TLS maturity, density, and immune infiltration (CD4+, CD8+, CD20+, CD21+ cells). Matched biopsies confirmed NHT enhanced TLS detection, maturation, and intra-TLS CD8+ T cell infiltration. Transcriptomics revealed upregulated CD4, CD8, CD20, and FOXP3 post-NHT. In mice, androgen deprivation therapy (ADT) increased immune infiltration, and anti-PD1/ADT combination improved tumor response.ConclusionOur findings demonstrate that TLS serve as a favorable prognostic biomarker in prostate cancer. NHT enhances TLS formation, maturation, and immune cell infiltration, suggesting a synergistic role for androgen deprivation in shaping the tumor immune microenvironment. The improved anti-tumor response with combined anti-PD1 and ADT highlights the potential of immunotherapy-endocrine therapy combinations as a promising treatment strategy for PCa.